Subfrontal Infrachiasmatic Approach to a Craniopharyngioma Resection: 2-Dimensional Operative Video. Issue 3 (5th February 2019) - Aldave, Guillermo; Zinn, Pascal; Whitehead, William E
Abstract: Craniopharyngioma constitutes one of the most challenging tumors. The surgery may be the definitive treatment and multiple approaches have been described based on different anatomical considerations. The choice of the right approach is the key to optimize the resection and minimize the risks. Besides, the presentation of this tumor in the pediatric population can carry additional challenges that are not present in adults, like the absence of pneumatization of the sphenoid bone for an endoscopic endonasal approach. In this video, we present a case of a 6-yr-old girl with a large sellar-suprasellar craniopharyngioma. The fact that the sphenoid was not pneumatized and the chiasm was elevated 1.2 cm from the planum sphenoidal were some of the reasons to choose a subfrontal infrachiasmatic approach as we discuss and we show in the video. This approach has not been very well established in the literature but we demonstrate it can become a good alternative for a particular type of sellar-suprasellar tumors. Appropriate video authorization consent was obtained from the parent of the patient.